2021
DOI: 10.1002/smll.202102711
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nanomaterials in Isothermal Nucleic Acid Amplification

Abstract: Because of high sensitivity and specificity, isothermal nucleic acid amplification are widely applied in many fields. To facilitate and improve their performance, various nanomaterials, like nanoparticles, nanowires, nanosheets, nanotubes, and nanoporous films are introduced in isothermal nucleic acid amplification. However, the specific application, roles, and prospect of nanomaterials in isothermal nucleic acid amplification have not been comprehensively reviewed. Here, the application of different nanomater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 178 publications
(149 reference statements)
0
20
0
Order By: Relevance
“…Nanomaterials play a crucial role in NA detection, with detection results showing high performance in terms of sensitivity and selectivity. A lot of the literature reveals that modified nanomaterials not only improve detection capability (about 10–1000 fold compared to routine PCR), but also address the complexity of the sample ( Chen et al, 2020 ; Fang et al, 2021 ; Liu et al, 2021 ; Zhang C et al, 2022 ), such as in the detection of Salmonella Typhimurium in complex food environments using a novel fluorescent platform of DNA-stabilized silver nanoclusters. The authors assessed the effectiveness of the main method in terms of sensitivity, specificity, and detection rate in complex samples and their results showed that the detection rate had a linear concentration range of Salmonella Typhimurium from 4.6×10 2 to 4.6 × 10 7 CFU/ml, with the limit of detection reaching 6.6 × 10 2 CFU/ml in food samples ( Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nanomaterials play a crucial role in NA detection, with detection results showing high performance in terms of sensitivity and selectivity. A lot of the literature reveals that modified nanomaterials not only improve detection capability (about 10–1000 fold compared to routine PCR), but also address the complexity of the sample ( Chen et al, 2020 ; Fang et al, 2021 ; Liu et al, 2021 ; Zhang C et al, 2022 ), such as in the detection of Salmonella Typhimurium in complex food environments using a novel fluorescent platform of DNA-stabilized silver nanoclusters. The authors assessed the effectiveness of the main method in terms of sensitivity, specificity, and detection rate in complex samples and their results showed that the detection rate had a linear concentration range of Salmonella Typhimurium from 4.6×10 2 to 4.6 × 10 7 CFU/ml, with the limit of detection reaching 6.6 × 10 2 CFU/ml in food samples ( Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Literature reports on the production of MgO 2 nanosheets have been published via a microemulsion system, where cyclohexane and CO-5 2 0 were added to an MgCl 2 solution [200,[202][203][204]. After 30 minutes of stirring, ammonium hydroxide was quickly introduced to generate Mg(OH) 2 and stirred for another 30 minutes.…”
Section: Synthetic Procedures For Metal Peroxidesmentioning
confidence: 99%
“…Nucleic acid test such as reverse transcriptase quantitative polymerase chain reaction (RT-qPCR) is currently considered as the gold standard for SARS-CoV-2 diagnosis ( Yu et al, 2021 , Zhou et al, 2022 ). Reverse transcription loop-mediated isothermal amplification (RT-LAMP) has been applied for SARS-CoV-2 detection due to its isothermal feature and fast amplification rate, which is more suitable for the rapid and point-of-care test (POCT) ( Orooji et al, 2021 , Viet Loan Dao et al, 2020 , Zhang et al, 2021 ). However, quantification by RT-qPCR or RT-qLAMP relies on the accurate and stable external standards or references, with a large variability reported even within trained laboratories.…”
Section: Introductionmentioning
confidence: 99%